Prospek Relasi Dewan Perwakilan Daerah Dengan Partai Politik - Bagir Manan; Indra Perwira; Mei Susanto (Jurnal Hukum IUS QUIA IUSTUM, 2021)
This article analyzes the relationship between the Regional Representative Council (DPD) and political parties that are often confronted diametrically. The questions presented, what is the historical factor for the formation of the DPD and the comparison of the practices of several countries in relation to regional representative bodies and political parties? What are the prospects for the relationship between the DPD and political parties in the future? This article aims to provide a different perspective on the relationship between the DPD and political parties from the historical, comparative and conception point of regional representation bodies. Through the socio-legal method, it was concluded that, first, historically the formation of the DPD was designed to be filled by individuals, not political parties. However, the practice of some countries shows that regional representative bodies generally cannot be separated from political parties. The lesson is that separating the DPD and political parties "strictly" can be said to always be violated because it is not in accordance with the natural conditions of filling the DPD directly by the people, who are influenced by the strength of the network and political parties. Second, whether or not there are political party affiliations in the DPD will not have a significant impact due to the limited authority of the DPD, so what is needed is the granting of significant DPD authority in the legislative process and supervision through the bicameral model. Thus, the prospect of the relationship between the DPD and political parties in the future can contribute to each other according to the DPD's already significant authority while still providing space for individuals